EDUKASI KESEHATAN REPRODUKSI SEBAGAI UPAYA PENCEGAHAN PERNIKAHAN DINI PADA REMAJA - Yuwanti; Feri Dwi Aviani (LPPM AN Nuur, 2025)
Background: Child marriage is still a significant issue affecting adolescent health and social well-being. This practice can lead to reproductive complications, psychological challenges, and social difficulties. Delivering reproductive health education is considered an effective approach to reduce its occurrence Purpose: to improve adolecents’ knowledge of reproductive health as preventive effort against early marriage. Method: this community service program was conducted through health education sessions using counselling method. Results: the activity increased adolescents knowledge and awareness of reproductive health and the negative consequence of early marriage. Conclusion: Reproductive health education effectively enchance adolescents’ knowledge and may contribute to prevention of early marriage.